2020
DOI: 10.21203/rs.2.19580/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Out-of-hours workload among Norwegian general practitioners – an observational study

Abstract: Background: Repeated studies of working hours among Norwegian regular general practitioners (RGPs) have shown that the average total number of weekly working hours has remained unchanged since 1994 and up until 2014. For both male and female RGPs, the mean total weekly working hours amounted to almost 50 hours in 2014. In recent years, Norwegian RGPs have become increasingly dissatisfied. They experience significantly increased workload without compensation in the form of more doctors or better payment. A stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This study adds to earlier research that has mainly used self‐reported data, 9 cross‐sectional design, 10 few medical specialties, prevalence of injuries, 15 or only needle‐stick injuries. Our analysis, using 7‐day windows to estimate the likelihood of occupational injuries, suggested that shift intensity, as indicated by the number of consecutive working days and number of on‐call shifts, increased the likelihood of occupational injury.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This study adds to earlier research that has mainly used self‐reported data, 9 cross‐sectional design, 10 few medical specialties, prevalence of injuries, 15 or only needle‐stick injuries. Our analysis, using 7‐day windows to estimate the likelihood of occupational injuries, suggested that shift intensity, as indicated by the number of consecutive working days and number of on‐call shifts, increased the likelihood of occupational injury.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies of physicians’ working hours and on‐call work have utilized self‐reported data, which are prone to recall or reporting bias 9 . Further limitations include the use of cross‐sectional designs 10 and study populations that cover only a few medical specialties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation